Production and characterization of monoclonal antibodies to tetanus toxin. - Sheppard, A J (1984)
Monoclonal antibodies against tetanus toxin were produced to obtain highly specific antisera. Ten hybridoma cell lines producing monoclonal antibodies were derived from the fusion of rat myeloma cells and spleen cells from rats immunized with tetanus toxoid. Eight produced monoclonal antibodies specific for determinants on toxin and toxoid, whereas two were specific only for determinants on the toxoid. The antibodies produced by hybridomas were characterized by determination of the class of light and heavy chain components, epitope specificity, toxin neutralization, and subunit specificity. All of the antibodies contained kappa light chain, eight contained the gamma 1 heavy chain, and the remaining two contained the gamma 2a heavy chain. Five distinct epitopes were indicated by competition assay of paired monoclonal antibodies, and 4 of the 10 monoclonal antibodies neutralized the in vivo activity of tetanus toxin. The four neutralizing monoclonal antibodies and one other were specific for the C fragment of the heavy chain of the toxin molecule.